TRANSFORMATION OF THE GANJURAN CHURCH COMPLEX: A TYPOLOGICAL STUDY - Santosa, Adi (Dimensi Interior, 2012)
The Ganjuran Church, a parish church located in South of Yogyakarta, is an interesting object related to typological studies. This study reveals that since its first establishment, Ganjuran Church has experienced three phases of development. From those phases, buildings in Ganjuran complex can be compiled into five types: kampong, limasan and joglo houses, Javanese Hindu-Budhism temple and Roman basilica. Meanwhile, architectural transformations occurs in the monument and church areas. This study also interprets that typological analysis is not only able to reveal architectural transformations, but also cultural transformations. In this context, typology is not only related to technical matters such as form and construction but also non-technical matters such as cultural perception and symbolism.